Factors associated with 48 hours revisit in schizophrenia patients at psychiatric emergency department, Srithanya hospital. - Saenchitta, Pongpreeda; Jariyavilas, Apichat; Silpakit, Orawan (Academic Psychiatry and Psychology Journal, 2025)
Objectives:The objective was to study the characteristics of schizophrenia patients and factors associated with inpatient or outpatient care revisiting within 48 hours at the emergency psychiatry department of Srithanya hospital. Materials and methods: This study was a cross-sectional study of 128 schizophrenia patients undergone treatment from 1 October 2020 to 30 September 2023. The data was retrieved from medical records (e.g. disease factor, patient factor, medical service factor, family and community factor) and further analyzed with descriptive statistics including frequency, standard deviation, chi-square test, and multivariate logistic regression analysis to identify factors associated with inpatient or outpatient care Results:The sample consisted of 128 schizophrenia patients, and most of them were male (68.8%). The average time for revisit was 21.5 ± 14.9 hours, and the most crucial factor influencing revisit was disease-related factor (46.9%). Additionally, symptoms of psychosis were associated with inpatient care (95% CI: 1.09 - 5.58), while medication side effects were significantly associated with outpatient care (95% CI: 0.00 - 0.31). On the other hand, there was no significant association between 48 hours revisit in patient, medical service, family and community factors. Conclusion: Most schizophrenia patients readmitted as inpatients to the emergency psychiatry department at Srithanya Hospital within 48 hours were due to psychotic symptoms, and medication side effects was a significant disease-related factor associated with outpatient revisits.